Associations of office brachial blood pressure, office central blood pressure, and home brachial blood pressure with arterial stiffness. Issue 3 (31st January 2022) - Mizuno, Hiroyuki; Hoshide, Satoshi; Nozue, Ryoko; Shimbo, Daichi; Kario, Kazuomi
Abstract : Accurate blood pressure (BP) measurement is necessary for the evaluation and treatment of hypertension to prevent the progression of subclinical vascular disease, including arterial stiffness. We investigated the associations between brachial–ankle pulse wave velocity (baPWV), a measure of arterial stiffness, and each of office brachial systolic BP (SBP) with and without an observer present (attended or unattended office brachial SBP), attended or unattended office central SBP, and home brachial SBPs (specifically, the means of morning, evening, or morning–evening home brachial SBP) in patients being treated for hypertension. Measurements were performed among 70 adults (mean age, 67.0 ± 9.4 years; women, 51.4%) with a mean attended office brachial SBP of 127.6 ± 14.5 mmHg and mean baPWV of 16.3 ± 2.8 m/s. Univariate analysis showed that higher attended office brachial SBP, morning home brachial SBP, and morning–evening home brachial SBP were each statistically significantly associated with higher baPWV ( r = 0.25, P = 0.04; r = 0.37, P = 0.002; and r = 0.32, P = 0.006, respectively). Multiple linear regression analysis with adjustments for traditional cardiovascular risk factors showed that only morning home brachial SBP was statistically significantly associated with baPWV [ β = 0.06, 95% confidence interval (0.01–0.11), P = 0.02). In conclusion, higher morning home brachial SBP – but none of the office-measured SBP values – was associated with arterial stiffness.